Experimental Study on Limestone Cohesive Particle Model and Crushing Simulation - Huaiying Fang; Dawei Xing; Jianhong Yang; Fulin Liu; Junlong Chen; Jiansheng Li (Advances in Materials Science and Engineering)
This study investigates the effect of impact velocity and particle size on crushing characteristics. We use a discrete-element method simulation and construct cohesive limestone particles with internal microinterfaces and cracks for impact crushing experimentation. The simulation model follows the same process as the impact crushing experiment. Results show that, after crushing at impact velocities of 30 and 40 m/s, the simulated particle-size distribution curve matches experimental results as closely as 95%. For different particle sizes, results are more than 90% in agreement. These results indicate the feasibility of the cohesive-particle crushing simulation model. When the particle size is 15 mm, an approximate linear relationship exists on impact velocity and crushing ratio. For a constant impact velocity, the particle size of 18 mm results in the maximum crushing ratio.